THE INFLUENCE OF EXERCISE METHOD AND REACTIONS TIME TO SKILLS SPRINT 100 METERS - Raffly Henjilito; Moch. Asmawi; James Tangkudung (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The purpose of this research was determine the effect of free variables that the method of exercise and the moderator variable reaction time of the dependent variable of 100 meters. The research was done by using experimental method. Target population (research population) are male student of physical education, health and recreation islamic university of riau 2016/2017 123 people. Sampling was done by purposive sampling technique. The hypothesis is 1) difference between group of interval training method (A1) with group of continuous training method (A2) equal to 0,0245 < 0,05, mean h0 rejected. 2) The difference between group of interval training method (A1) and group of mixed exercise method (A3), value = 0,0015 < 0,05, means h0 rejected. 3) The difference between the continuous training method group (A2) and the mixed exercise method group (A3), worth = 0.1345 > 0.05, means h0 received. 4) The interaction effect of fo (AB) worth = 0,000 < 0.05 means h0 is rejected. 5) Differences in 100 meters of skill results between interval training methods with high reaction time and continuous training method with high reaction time (A1B1 - A2B1) valued at 0.000 < 0.05 means h0 is rejected. 6) Differences in 100 meters of skill result between interval training method with high reaction time and mixed reaction method with high reaction time (A1B1 - A3B1). Value = 0,000 < 0,05 means h0 is rejected. 7) Differences in 100 meter running skills results between continuous training method with high reaction time and high mixed reaction method (A2B1 - A3B1) method = 0,000 < 0,05 means h0 is rejected. 8) Differences in the results of 100 meter running skills between interval training methods with low reaction time and continuous training method with low reaction time (A1B2 - A2B2) valued = 0.413 > 0.05 means h0 received. 9) Differences in the results of 100 meter running skills between interval training methods with low reaction time and mixed reaction method with low reaction time (A1B2 - A3B2) worth = 0.0155 < 0.05 means h0 is rejected. 10) The difference of 100 meter running skill result between continuous training method with low reaction time and mixed reaction method with low reaction time(A2B2 - A3B2) worth = 0,026 < 0,05 means h0 is rejected. Keywords: Skills Sprint 100 Meters, Exercise Method And Reaction Time